2020
DOI: 10.1029/2019ja027318
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Martian Circulation Patterns and Atmospheric Tides Through MAVEN/IUVS Nightglow Observations

Abstract: We report results from a study of two consecutive Martian years of imaging observations of nitric oxide ultraviolet nightglow by the Imaging Ultraviolet Spectrograph (IUVS) on the Mars Atmosphere and Volatile Evolution (MAVEN) mission spacecraft. The emission arises from recombination of N and O atoms in Mars' nightside mesosphere. The brightness traces the reaction rate as opposed to the abundance of constituents, revealing where circulation patterns concentrate N and O and enhance recombination. Emissions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…The observation files used in this work are identified as “periapse” version 13 of the Level 1B data available at the PDS IUVS repository under “Limb Scan … Processed Data.” The data processing methodology for nightside observations is described in detail in Schneider et al. (2020). Below we describe additional processing steps unique to this auroral study.…”
Section: Observation and Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation files used in this work are identified as “periapse” version 13 of the Level 1B data available at the PDS IUVS repository under “Limb Scan … Processed Data.” The data processing methodology for nightside observations is described in detail in Schneider et al. (2020). Below we describe additional processing steps unique to this auroral study.…”
Section: Observation and Analysis Methodsmentioning
confidence: 99%
“…The instrumental fitted spectra were converted to kiloRayleighs (abbreviated kR) per nm using stellar calibration observations (Schneider et al., 2020), and then summed over the spectral feature to yield the emission brightness in kR. Random uncertainties in a pixel's fitted intensities were calculated based on the combination of photon statistics and detector background noise in the original spectrum.…”
Section: Observation and Analysis Methodsmentioning
confidence: 99%
“…The MUV brightness data carry an estimated systematic uncertainty of 30%. Level 1 C (L1C; Schneider et al., 2020; Schneider21) cleaned data, archived with the NASA Planetary Data System (PDS), have been used to detect auroral signatures (see Section 2.2) and quantify the auroral emissions (see Section 3).…”
Section: The Maven‐iuvs Auroral Data Setmentioning
confidence: 99%
“…Schneider et al. (2020) identified the presence of wavenumber‐3 structure in the NO nightglow brightness derived from MAVEN‐IUVS in the middle atmosphere at low equatorial latitudes. On further examining the phase of the wave with local time, the authors found that the predominant tide underlying the wavenumber‐3 structure is the eastward moving diurnal tide with zonal wavenumber s = 2 (DE2).…”
Section: Introductionmentioning
confidence: 99%